Association of peak expiratory flow with motoric cognitive risk syndrome among older adults - Xu, Hui; Gong, Xiangwen; Cui, Kaiwang; Li, Xuerui; Chen, Long; Lu, Yiyi; Liao, Yangfang; Liu, Jianping (Frontiers in Aging Neuroscience, 2024)
The association between lung function and motoric cognitive risk syndrome (MCR) is unclear. We aimed to explore the association of peak expiratory flow (PEF) with MCR using cross-sectional and longitudinal analyses.Methods: Within the CHARLS, 5095 participants were included in the cross-sectional analysis, and 4340 MCR-free participants were included in the longitudinal analysis. The PEF was assessed with a lung peak flow meter. MCR was characterized by cognitive complaints and a slow walking speed with normal mobility and without dementia. Logistic regression, Cox regression, and Laplace regression models were employed for data analysis.In this cross-sectional study, logistic regression analyses revealed that continuous PEF was associated with MCR (odds ratio [OR], 0.998; 95% confidence interval [CI], 0.998, 0.999), and the ORs (95% CIs) of MCR prevalence were 0.857 (0.693, 1.061) for the middle tertile and 0.665 (0.524, 0.845) for the highest tertile compared to the lowest tertile. In a longitudinal cohort study, continuous PEF was dose-dependently associated with the risk of MCR. Compared with those in the lowest tertile of PEF, the hazard ratios (95% CIs) of incident MCR were 0.827 (0.661, 1,036) for the middle tertile and 0.576 (0.432, 0.767) for the highest tertile. Furthermore, compared with the lowest tertile, the highest tertile was associated with a delayed onset time of MCR of 0.484 (95% CI: 0.151, 0.817) years.Conclusions: A higher PEF was related to a lower prevalence of MCR and a lower risk for MCR, and a higher PEF also prolonged the onset time of MCR.